2016
DOI: 10.1109/tcsvt.2015.2477916
|View full text |Cite
|
Sign up to set email alerts
|

Video Quality Evaluation Methodology and Verification Testing of HEVC Compression Performance

Abstract: The High Efficiency Video Coding (HEVC) standard (ITU-T H.265 and ISO/IEC 23008-2) has been developed with the main goal of providing significantly improved video compression compared to its predecessors. In order to evaluate this goal, verification tests were conducted by the Joint Collaborative Team on Video Coding (JCT-VC) of ITU-T SG 16 WP 3 and ISO/IEC JTC 1/SC 29. This paper presents the subjective and objective results of a verification test where the performance of the new standard is compared with its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(92 citation statements)
references
References 17 publications
1
86
0
Order By: Relevance
“…We note that conventional molecular visualization approaches based on planar projections and OpenGL rasterization often have difficulty maintaining high interactivity when viewing large complexes such as the HIV-1 capsid scene. Recently, Tan et al have reported that HEVC/H.265 video encoding offers up to a 59% reduction in bit rate as compared with MPEG-4 AVC/H.264 for perceptually comparable video quality [53]. HEVC/H.265 encoding is a significant future opportunity for increasing streaming performance at 4K (3840 × 2160) image resolutions and beyond.…”
Section: Performance Results and Discussionmentioning
confidence: 99%
“…We note that conventional molecular visualization approaches based on planar projections and OpenGL rasterization often have difficulty maintaining high interactivity when viewing large complexes such as the HIV-1 capsid scene. Recently, Tan et al have reported that HEVC/H.265 video encoding offers up to a 59% reduction in bit rate as compared with MPEG-4 AVC/H.264 for perceptually comparable video quality [53]. HEVC/H.265 encoding is a significant future opportunity for increasing streaming performance at 4K (3840 × 2160) image resolutions and beyond.…”
Section: Performance Results and Discussionmentioning
confidence: 99%
“…MPEG-H/H.265 suite [41,42], -which is focused on the delivery of media in heterogeneous environments, IP networks and digital broadcasting networks-includes HEVC compression format (high efficiency video coding), which is more efficient in mobile applications and supports hi-res 4k/8k, 3D TV. It also includes the MMT standard (The MPEG Media Transport) that defines the Encapsulation, Delivery, and Signaling, as well as the application layer forward error correction (AL-FEC), among others.…”
Section: Encoders and Transcoding Technologiesmentioning
confidence: 99%
“…Based on these typical algorithms, we can arrive at a primary conclusion. In addition, some video quality assessment metrics were proposed [14], [15]. Traditional full reference image quality assessment often makes use of the subtraction between distortion image and reference image [16].…”
Section: Introductionmentioning
confidence: 99%